A Global Perspective of Food Market Integration: A Review. Issue 1 (2nd April 2016) - Kabbiri, Ronald; Dora, Manoj; Elepu, Gabriel; Gellynck, Xavier
ABSTRACT: This paper analyses the state of the art research on food market integration, classifies it and provides a comprehensive bibliography for researchers with interest in market integration. A thorough review of literature published between 1990 and 2014 on food market integration generated 65 articles for in-depth analysis. Findings show that the majority of research has concentrated relatively more on identifying the degree of linkages among the markets but not on its implications. The paper also identifies the following factors as very important in increasing/ decreasing the degree of market integration: physical infrastructure, market institutions, information, competition, market power, trade, social capital, public/ government intervention and export restrictions/ban. The paper further identifies several areas for future research.